Pengaruh Peran Penyuluh Agama Islam Terhadap Tingkat Pemahaman Keluarga Sakinah Bagi Calon Pengantin Di Kec. Banyuwangi - Rajwanadia Nurwahidah; Khoirotun Nisa; Ach. Firman Ilahi (Jurnal Ilmu Bimbingan dan Konseling, 2025)
This research aims to examines the influence of the role of Islamic Religious Counsellors (PAI) on the level of understanding of the Sakinah Family concept among prospective brides and grooms (catin) at the Office of Religious Affairs (KUA) in Banyuwangi District. The Sakinah family is the fundamental goal of Islamic marriage, but achieving it often requires proper guidance due to prevalent pre-marital and spousal misunderstanding issues. PAIs are essential for equipping couples with the necessary knowledge on faith, piety, and noble character (akhlakul karimah). The study utilizes a quantitative correlational method involving 15 prospective couples or 30 persons from the KUA of Banyuwangi District. Data was efficiently collected using a QR-code converted from Google Form administered after the couples attended Marriage Guidance. Analysis was conducted using simple linear regression. The PAI's multifaceted role is defined as Educator (teaching rights and duties), Counselor (addressing concerns and conflicts), and Facilitator (empowering practical skills). The results demonstrate that the role of PAI has a strong and significant influence on the couples' level of understanding of the Sakinah family. The PAI's contribution accounts for 65.9% of the variance in understanding ($Sig. = 0.000$). The positive coefficient ($B = 1.931$) confirms a direct relationship: increased quality or presence of PAI guidance significantly raises the level of Sakinah family understanding among prospective couples. This underscores the critical importance of PAI in marriage preparation.